Détérioration des salaires des nouveaux immigrants au Québec par rapport à l'Ontario et à la Colombie-Britannique - Boudarbat, Brahim; Boulet, Maude (Choices (Institute for Research on Public Policy), 2007)
Notre étude a un double objectif. Elle vise d’abord à comparer l’évolution des salaires d’entrée des immigrants au Québec par rapport à l’Ontario et à la Colombie-Britannique. Ensemble, ces trois provinces ont accueilli 89,5 % des immigrants arrivés au Canada au cours des années 1990 (Statistique Canada 2003). Ensuite, notre analyse s’emploie à expliquer les changements observés à cet égard dans chacune des trois provinces en considérant notamment le rôle des trois facteurs relevés dans la littérature, à savoir la région d’origine et les compétences linguistiques, le rendement de l’expérience acquise à l’étranger et le cycle économique. -- Introduction
Keywords: British Columbia; British Columbia. Immigrants; Economic conditions. Immigrants; Economic conditions. Wages; Foreign workers; Ontario; Ontario. Wages; Wages

La pendaison d'Angélique : l'histoire de l'esclavage au Canada et de l'incendie de Montréal - Cooper, Afua (Éditions de l'Homme, 2007)
Dans la soirée du samedi 10 avril 1734, Montréal brûle. L'esclave Marie-Joseph- Angélique est traduite devant la justice et accusée d'avoir mis le feu. Soumise à la question extraordinaire, forme de torture atroce pendant laquelle on brise les os des jambes, elle craque et avoue avoir commis cet incendie criminel. Puis, elle est pendue. Angélique entre dans l'histoire canadienne en tant que criminelle. Cependant, son procès nous offre une occasion unique de raconter sa vie d'esclave, une vie dont on n'aurait pas entendu parler autrement. Afua Cooper fait revivre brillamment un chapitre méconnu de l'histoire du Canada, celui d'une Noire rebelle d'origine portugaise qui a cherché à briser ses chaînes. En nous présentant le vécu de cette jeune femme, elle met en lumière ce qui l'a sans doute poussée à commettre pareil crime. Par le fait même, elle détruit le mythe d'un Canada considéré comme un paradis pour les Noirs ayant échappé à l'esclavagisme des États-Unis. L'histoire d'Angélique est le plus ancien récit à propos de l'esclavage dans le Nouveau Monde. En lui consacrant cet ouvrage, Afua Cooper apporte une importante contribution à l'historiographie canadienne et met en perspective l'esclavage accepté légalement et culturellement au Canada. --Publisher's description
Keywords: Marie-Joseph-Angélique

Collective Bargaining in Canada: Human Right or Canadian Illusion? - Fudge, Derek (Fernwood, 2007)
Recounting the cuts to freedom of association and the collective bargaining process across Canada since the 1980s, this study challenges the notion that Canada is an international champion of human rights. With documentation on the assaults to the rights of Canadian workers, this text considers the ways governments intervene to stop the collective bargaining process and evaluates topics such as the history of collective bargaining in Canada, the role of the International Labor Office, and the future hope of restoring rights and fairness to labor laws. --Publisher's description
Keywords: Collective bargaining; Labor laws and legislation

Organizing the Transnational: Labour, Politics, and Social Change - Goldring, Luin; Krishnamurti, Sailaja (UBC Press, 2007)
Growing recognition of transnational practices and identities is changing the way scholars and activists ask questions about migration. Organizing the Transnational articulates a multi-level cultural politics of transnationalism to frame contemporary analyses of immigration and diasporas. With chapters by academics and activists working from diverse perspectives, the volume moves beyond the conventional focus on states and migrants to consider a wide array of institutions, actors, and forms of mobilization that shape transnational engagements and communities. Its unique approach will inform the work of researchers, practitioners, and activists interested in the dynamics of transnational social spaces. --Publisher's description
Keywords: Asians; Asians Canada; Asiatiques Canada; Asien; Canada; Changement social Canada; Community organization; Community organization Canada; Einwanderung; Ethnicity; Ethnicity Canada; Ethnicité Canada; Etnicitet Kanada; Hispanos; Immigrants; Immigrants Canada; Immigration Kanada; Kanada; Latin Americans; Latin Americans Canada; Latino-Américains Canada; Organisation communautaire Canada; Social change; Social change Canada; Social förändring Kanada; Sozialer Wandel; Transnationale Politik; Transnationalism; Transnationalisme

Guarding the Gates: The Canadian Labour Movement and Immigration, 1872-1934 - Goutor, David (UBC Press, 2007)
From the 1870s until the Great Depression, immigration was often the question of the hour in Canada. Politicians, the media, and an array of interest groups viewed it as essential to nation building, developing the economy, and shaping Canada’s social and cultural character. One of the groups most determined to influence public debate and government policy on the issue was organized labour, and unionists were often relentless critics of immigrant recruitment. Guarding the Gates is the first detailed study of Canadian labour leaders’ approach to immigration, a key battleground in struggles between different political factions within the labour movement. --Publisher's description
Keywords: Emigration and immigration; Employment; Government policy; History; Immigrants; Labor Unions; Race discrimination

Capital and Labour in the British Columbia Forest Industry, 1934-74 - Hak, Gordon H. (Gordon Hugh) (UBC Press, 2007)
The history of British Columbia’s economy in the twentieth century is inextricably bound to the development of the forest industry. In this comprehensive study, Gordon Hak approaches the forest industry from the perspectives of workers and employers, examining the two main sets of institutions that structured the relationship during the Fordist era: the companies and the unions. Drawing on theories of the labour process, Fordism, and discursive subjectivity, Hak relates daily routines of production and profit-making to broader forces of unionism, business ideology, ecological protest, technological change, and corporate concentration. The struggle of the small-business sector to survive in the face of corporate growth, the history of the industry on the Coast and in the Interior, the transformations in capital-labour relations during the period, government forest policy, and the forest industry’s encounter with the emerging environmental movement are all considered in this eloquent analysis. With its critical historical perspective, Capital and Labour in the British Columbia Forest Industry will be essential reading for anyone interested in the business, natural resource, political, social, and labour history of the province. --Publisher's description
Keywords: Forests and forestry -- British Columbia -- History

Race, Racialization, and Antiracism in Canada and Beyond - Johnson, Genevieve Fuji; Enomoto, Randy; Canadian Ethnocultural Council; National Association of Japanese Canadians; End Racism! Activism for the 21st Century Conference (2000 : Vancouver, BC) (University of Toronto Press, 2007)
This multidisciplinary volume brings together scholars and activists to examine expressions of racism in contemporary policy areas, including education, labour, immigration, media, and urban planning. While anti-racist struggles during the twentieth century were largely pitched against overt forms of racism (e.g., pogroms, genocide, segregation, apartheid, and 'ethnic cleansing'), it has become increasingly apparent that there are other, less visible, forms of racism. These subtler incarnations are of special interest to the contributors. The intent of Race, Racialization, and Antiracism in Canada and Beyond is to probe systemic forms of racism, as well as to suggest strategies for addressing them. The collection is organized by themes pertinent to political and social expressions of racism in Canada and the wider world, such as the state and its mediation of race, education and the perpetuation of racist marginalization, and the role of the media. The contributors argue that, in order to effectively combat racism, various methodological approaches are required, approaches that are reflective of the diversity of the world we seek to understand. -- Publisher's description. Contents: Introduction / Audrey Kobayashi and Genevieve Fuji Johnson -- Negotiating school: marginalized students' participation in their education process / Carl E. James -- Multicultural education: teacher candidates speak out / Donatille Mujawamariya -- The sky didn't fall: organizing to combat racism in the workplace -- the case of the alliance for employment equity / Abigail B. Bakan and Audrey Kobayashi -- Employment conditions of racial minorities in Canada: how bad is the problem of discrimination? / Mohammed A. Al-Waqfi and Harish C. Jain -- Immigrant women's activism: the past thirty-five years / Tania Das Gupta -- Critical discourse analysis: a powerful but flawed tool? / Frances Henry and Carol Tator -- Special plus and special negative: the conflict between perceptions and applications of 'special status' in Canada / Howard Ramos -- Who belongs? Expoloring race and racialization in Canada / Leanne Taylor, Carl E. James, and Roger Saul -- The racialization of space: producng surrey / Gurpreet Singh Johal -- Raceless states / David Theo Goldberg -- Multi-identifications and transformations: reaching beyond racial and ethnic reductionisms / Philomena Essed.
Keywords: Canada; Employment discrimination; Equity; Racism

Corporate Wasteland: The Landscape and Memory of Deindustrialization - Lewis, David; High, Steven C. (Between the Lines, 2007)
Deindustrialization is not simply an economic process; it is also a social and cultural phenomenon. The rusting detritus of our industrial past — the wrecked halls of factories, abandoned machinery too large to remove, and now useless infrastructures — has for decades been a part of the North American landscape. Through a unique blend of oral history, photographs, and interpretive essays, [this book] investigates this fascinating terrain and the phenomenon of its loss and rediscovery. --Publisher's description

Industrial Relations in Canada - McQuarrie, Fiona A. E. (Wiley and Sons Canada, 2007)
Makes it easier to understand the complex and sometimes controversial field of industrial relations. How? Its unique process-oriented approach gives you a clear road map by illustrating how and why unions are formed, and introduces you to the Canadian industrial relations system and the forces that shape it. --Publisher's description
Keywords: Industrial relations -- Canada -- Textbooks

Defining Work: Gender, Professional Work, and the Case of Rural Clergy - Mellow, Muriel (McGill-Queen's University Press, 2007)
An illuminating study of how gender and work intersect among the rural clergy. For rural clergy, the lines between private life and professional life can blur. Their offices are often in their homes, parishioners are also neighbours, and professional duties are intertwined with emotional caregiving and volunteer activity. In a society that defines work as paid, public, and intellectual the ambiguity inherent in the life of the rural clergy poses unique challenges. Muriel Mellow considers how men and women in this occupational group conceptualize "work" in the context of their unique circumstances and shows how their experience raises questions for feminist theories of work. Based on interviews with forty rural Protestant clergy, Mellow argues that male and female clergy challenge gendered definitions of work by focusing on obligation, context, visibility, and time. She also considers how clergy's work is shaped by the rural setting, arguing that we must consider how work is "placed" as well as gendered. --Publisher's description

Working People: An Illustrated History of the Canadian Labour Movement - Morton, Desmond (McGill-Queen's University Press, 2007)
From the dock workers of Saint John in 1812 to teenage "crews" at McDonald's today, Canada's trade union movement has a long, exciting history. Working People tells the story of the men and women in the labour movement in Canada and their struggle for security, dignity, and influence in our society. Desmond Morton highlights the great events of labour history - the 1902 meeting that enabled international unions to dominate Canadian unionism for seventy years, the Winnipeg General Strike of 1919, and an obscure 1944 order-in-council that became the labour's charter of rights and freedoms. He describes the romantic idealism of the Knights of Labor in the 1880s and looks at "new model" unions that used their members' dues and savings to fight powerful employers. Working People explores the clash between idealists, who fought for socialism, industrial democracy, and equality for women and men, and the realists who wrestled with the human realities of self-interest, prejudice, and fear. Morton tells us about Canadians who deserve to be better known - Phillips Thompson, Helena Gutteridge, Lynn Williams, Huguette Plamondon, Mabel Marlowe, Madeleine Parent, and a hundred others whose struggle to reconcile idealism and reality shaped Canada more than they could ever know. -- Publisher's description. Contents: Working people -- Getting organized -- International ideas -- Political movement -- Labour reformers -- Hinterland labour -- Trades and labour -- Gompers's shadow -- Business, labour, and governments -- Labour radicals -- Labour and the first World War -- Western revolt -- Unroaring twenties -- Surviving the depression -- Industrial unionism -- Fighting Hitler and management -- "People coming into their own" -- No falling back -- Struggle for allegiance -- Merger movement -- Times of frustration -- Prosperity and discontent -- Public Interest, Public Service -- Justice and nationalism -- Quebec and the common front -- Scapegoat for inflation -- Recession and hard times -- Levelling the playing field -- Struggling to the millennium -- Millennial achievements -- Graphs: Changes in the labour movement.
Keywords: Labor Unions; Labor movement; Working class

Confrontation, Struggle and Transformation: Organized Labour in the St. Catharines Area - Patrias, Carmela; Savage, Larry (Past CCLH Publications, 2007)
Confrontation, Struggle and Transformation is the story of working women and men in the St. Catharines area from the mid-1800s to the present. The study explores the labour movement's fight to survive and thrive in the Niagara region. Thanks to extensive quotations from interviews, archival sources and local newspapers, the story unfolds, in part, through the voices of the people themselves: workers who fought for unions, community members who supported them and employers who opposed them. --Publisher's description
Keywords: Discrimination in employment; History; Labor Unions; Labor movement; Political activity

Equity, Diversity, and Canadian Labour - Rayside, David M.; Hunt, Gerald (University of Toronto Press, 2007)
The Canadian labour movement has undergone several fundamental changes in response to demands for greater inclusion and representation by women, visible and sexual minorities, and people with disabilities. Equity, Diversity, and Canadian Labour explores the specific challenges put to outmoded conceptions of labour, charting the effort made towards establishing a more inclusive vision of labour in Canada. The study concludes that the Canadian labour movement has seen a fair amount of progress in this regard, though it still faces persistent impediments to equity and suffers from an uneven responsiveness within and across diversity issues. This collection of original essays brings together contributors from a variety of backgrounds womens studies, political science, sociology, industrial relations, and the labour movement itself. They provide detailed analyses of significant changes in union policies, practices, and cultures as viewed through different disciplinary lenses. With reference to gender, race, disability, and sexuality, the volume assesses the status of labour diversity in Canada and suggests what still needs to be done to advance the equity project. --Publisher's description. --Publisher's description. Contents: Looking back: A brief history of everything / Julie White -- Bargaining against the past: Fair pay, union practice, and the gender pay gap / Anne Forrest -- Union response to pay equity: A cautionary tale / Judy Haiven -- Labour's collective bargaining records on women's and family issues / Karen Bentham -- We are family: Labour responds to gay, lesbian, bisexual, and transgender workers / Gerald Hunt and Jonathan Eaton -- Broadening the labour movement's disability agenda / David Rayside and Fraser Valentine -- Racism and the labour movement / Tania Das Gupta -- Equity, diversity, and Canadian labour: A comparative perspective / David Rayside. Includes bibliographical references (pages 257-282).
Keywords: Activit politique. Mouvement ouvrier; Aspect social; Canada; Canada. Dmocratie syndicale; Canada. Genre/Form: Aufsatzsammlung; Canada. Labor movement; Canada. Labor movement. Labor union democracy. Labor unions; Canada. Labor union democracy; Canada. Labor unions; Canada. Pay equity; Canada. Syndicats; Canada. galit de rmunration; Labor unions; Political activity; Political activity. Labor unions; Social aspects; Social aspects. Pay equity. Arbeiterbewegung Gewerkschaft Syndicats

Labour and Employment Law in the Federal Public Service - Rootham, Christopher (Irwin Law, 2007)
[D]escribes the labour and employment law governing employees of Parliament, employees of government agencies, members of the RCMP, and most direct employees of the government (excluding members of the Canadian armed forces, judges, and employees of Crown corporations). Specifically, the book deals with the Public Service Labour Relations Act and the Public Service Employment Act. It also provides the leading cases and, where appropriate, a representative sample of decisions to explain or provide examples of particular points. The legal regime of the federal public service has undergone significant change in the past three years, and no other book addresses these significant changes. Part I of this book provides an overview of federal public service labour and employment law. Part II considers the normal labour law topics as they apply to direct employees of the government and employees of government agencies. Essentially, Part II of this book is about Part I of the Public Service Labour Relations Act. Part III concerns the terms and conditions of employment for both unionized and non-unionized employees — essentially, Part II of the Public Service Labour Relations Act. Part IV involves the legal regulation of the employment relationship in the federal public service — namely, the process for appointment to and within the federal public service. Part V of considers Crown servants — specifically RCMP members and parliamentary employees — who are not considered federal public servants for the purposes of the Public Service Labour Relations Act. Part VI considers the legal regulation of superannuation (pensions) for Crown servants and the role that courts play in the regulation of federal public service labour and employment law. --Publisher's description
Keywords: Canada; Civil service; Labor laws and legislation; Royal Canadian Mounted Police (RCMP)

Work in Tumultuous Times: Critical Perspectives - Shalla, Vivian; Clement, Wallace (McGill-Queen's University Press, 2007)
This interdisciplinary volume offers a powerful critique of how social structures and relations as well as ideologies shape workplaces, labour markets, and households in contemporary Canada. Contributors dissect recent transformations in work and expose the uncertainty, insecurity, and instability that increasingly characterize both paid and unpaid work. Using a progressive approach to political economy, contributors propose alternative policies and practices that might secure more decent livelihoods for workers and their families. -- Publisher's description
Keywords: Discrimination in employment; Job security; Labor